Pengaruh Dukungan Sosial Keluarga terhadap Motivasi Ibu Hamil dalam Menjaga Kesehatan Saat Kehamilan pada Masa Pandemi Covid-19 - Siska Nurul Abidah; Fritria Dwi Anggraini (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Maintaining health is a prerequisite for giving birth to a healthy baby. A pregnant woman needs motivation from the closest people so that it will have a positive impact. This study aims to determine the effect of family social support on the motivation of pregnant women in maintaining health during pregnancy during the COVID-19 pandemic. This study used descriptive analytic method with purposive sampling technique as many as 30 pregnant women. The research was conducted for 2 months, namely March-April 2021 in Kedungpring Village. The research instrument used a social support questionnaire consisting of 17 items and a motivation questionnaire. Both instruments consist of statements of support and statements of non-support. After the data was obtained, statistical tests were carried out using SPSS, namely the chi-square test. The results of the statistical test using the chi-square test obtained a significant value of 0.001 (p-value <0.05), meaning that there is an influence of family social support on the motivation of pregnant women to maintain health during pregnancy during the covid-19 pandemic. Pregnant women who get social support have a positive impact, namely feeling loved, cared for, protected and appreciated by their families so that pregnant women have the motivation to maintain health during pregnancy.